PHARMACOLOGICAL EFFECTS OF KB-28 COMPOUND UNDER CHRONIC IMMOBILIZATION STRESS CONDITIONS - Toziuk, O.Yu.; Kryvoviaz, O.V.; Ivko, T.I.; Voronkina, A.S. (World of Medicine and Biology, 2018)
According to experimental studies, sodium 2-(tetrazolo[1,5-c]quinazoline-5-ylthio)acetate (KB-28 compound) shows an expressive actoprotective action under normal conditions. The work investigated the influence of KB-28 compound in the conditions of chronic immobilization stress. The study revealed that the administration of this substance maintains a high level of performance in rats. This confirms the presence in KV-28 of actoprotective effect. It has been also proven that the action of the test substance is maintained in the complicated conditions of the experiment. In addition, it is established that a stress-protective effect is inherent to sodium 2-(tetrazolo[1,5-c]quinazoline-5-ylthio)acetate which was manifested by rapid adaptation of animals to chronic immobilization stress. The effectiveness of KB-28 compound was significantly superior to the reference substance on the 12th and 18th day of the study.